Analysis of The Level of Passenger Satisfaction With Services And Transport Facilities-Based Integration in Jakarta - Rifai, Andri Irfan; Arifin, Fachrul (NAROTAMA UNIVERSITY, Indonesia, 2020)
Rapid development in major cities in the world, especially in developing countries resulted in increased community activities. This has an impact on the community's increased traffic, causing a variety of impacts ranging from congestion, increased air pollution, wasted fuel, and reduced levels of comfort in traffic. The integration of public transport is one of the ways used by the Jakarta provincial government to address the level of congestion is getting worse. One of the areas in Jakarta that have been designated as regional transport integration is Dukuh Atas Region. Improved integration of services and public transport facilities can increase the interest of society to move from using private transport be using public transportation. This is the underlying researchers to conduct research on the assessment of the level of passenger satisfaction and service performance-based integration of transport facilities in Jakarta (Region case study Integration Dukuh Atas) and know the attributes that affect passenger satisfaction. Conclusions from the results of the study indicate that passengers are satisfied with the level of service and transportation integration facilities in the Dukuh Atas Region with CSI score 70,46%. But the need for some improvement of the performance attributes that are getting a low value, such as the integration between public transport schedules and timeliness of arrival and departure transportation.